Implementing trauma-informed care through social innovation in child welfare residential treatment centres serving elementary school children - Brend, Denise; Fréchette, Nicolas; Milord-Nadon, Arnaud; Harbinson, Tim; Collin-Vezina, Delphine (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2020)
Objectives: This article presents the theoretical basis, initial deployment strategies, and resulting preliminary findings of a program implemented in residential treatment centres (RCs) in child welfare. “Program Penguin” aimed to help workers develop trauma-informed attitudes and implement trauma-informed practices, make the workplace more responsive to the well-being of RC workers, and reduce the use of restraints and seclusion among school-aged children in RCs. Methods: Informed by the theories of complex trauma (National Child Traumatic Stress Network Complex Trauma Task Force, 2003), polyvicitimization (Finkelhor et al., 2007), Attachment, Self-Regulation and Competency (ARC; Blaustein & Kinniburgh, 2018) and Positive Behavioural Interventions and Supports (PBIS; Sugai & Horner, 2002), Program Penguin was developed and deployed using the social innovation approach (Fixsen et al. 2005). The key stages of social innovation will here be used to describe the implementation process. Results: Changes in practices were observed, RC worker attitudes towards trauma-informed care were assessed and showed strong effects between multiple covariables. RC worker support needs were identified, and a reduction in the use of restraints and seclusions was shown. Key strategies towards the development and maintenance of buy-in and meaningful change in practices are also described. Implications: Changes observed at all levels of this implementation suggest Programme Penguin is a promising approach, despite local issues that arose and the challenges inherent to program deployment within child protection settings. It appears a trauma-informed program using positive behavioural approaches and leveraging existing organizational strengths may impact intervention strategies, worker attitudes, and the use of restraints and seclusions against children in RCs.